Gd-Complex of a Rosmarinic Acid Conjugate as an Anti-Inflammatory Theranostic Agent via Reactive Oxygen Species Scavenging - Hee-Kyung Kim; Seonghwan Hwang; Bokyung Sung; Yeoun-Hee Kim; Yongmin Chang (MDPI AG, 2020)
Rosmarinic acid (RosA), an important polyphenol, is known for its antioxidant and anti-inflammatory activities. However, its application in theranostics has been rarely reported. Therefore, a new single-molecule anti-inflammatory theranostic compound containing RosA would be of great interest. A gadolinium (Gd) complex of 1,4,7,10-tetraazacyclododecane-1,4,7-trisacetic acid (DO3A) and RosA (Gd(DO3A-RosA)(H2O)) was synthesized and examined for use as a single-molecule theranostic agent. Its kinetic stability is comparable to that of clinically used macrocyclic magnetic resonance imaging contrast agents. In addition, its relaxivity is higher than that of structurally analogous Gd-BT-DO3A. This agent was evaluated for inflammatory targeting magnetic resonance contrast and showed strong and prolonged enhancement of imaging in inflamed tissues of mice. The theranostic agent also possesses antioxidant and anti-inflammatory activities, as evidenced by reactive oxygen species scavenging, superoxide dismutase activity, and inflammatory factors. The novel RosA-conjugated Gd complex is a promising theranostic agent for the imaging of inflamed tissues, as well as for the treatment of inflammation and oxidative stress.